Long-Term Outcome of Repetitive Transcranial Magnetic Stimulation in a Large Cohort of Patients With Cocaine-Use Disorder: An Observational Study - Madeo, Graziella; Terraneo, Alberto; Cardullo, Stefano; Gómez Pérez, Luis J.; Cellini, Nicola; Sarlo, Michela; Bonci, Antonello; Gallimberti, Luigi (Frontiers in Psychiatry, 2020)
Background: Cocaine is a psychostimulant drug used as performance enhancer throughout history. The prolonged use of cocaine is associated with addiction and a broad range of cognitive deficits. Currently, there are no medications proven to be effective for cocaine-use disorder (CocUD). Previous preliminary clinical work suggests some benefit from repetitive transcranial magnetic stimulation (rTMS) stimulating the prefrontal cortex (PFC), involved in inhibitory cognitive control, decision-making and attention. All published studies to date have been limited by small sample sizes and short follow-up times. Methods: This is a retrospective observational study of 284 outpatients (of whom 268 were men) meeting DSM-5 criteria for CocUD. At treatment entry, most were using cocaine every day or several times per week. All patients underwent three months of rTMS and were followed for up to 2 years, 8 months. Self-report, reports by family or significant others, and regular urine screens were used to assess drug use. Results: Median time to the first lapse (resumption of cocaine use) since the beginning of treatment was 91 days. For most patients, TMS was re-administered weekly, then monthly, throughout follow-up. The decrease in frequency of rTMS sessions was not accompanied by an increase in lapses to cocaine use. Mean frequency of cocaine use was less than 1·0 day/month (median 0), while serious rTMS-related adverse events were infrequent, consistent with published reports from smaller studies. Conclusions: This is the first follow-up study to show that rTMS treatment is accompanied by long-lasting reductions in cocaine use in a large cohort.